Same Issuer, Different Lenses: Divergence between Sharia Screening, Conventional ESG, and Maqasid -Based Islamic ESG in Indonesian Listed Companies - Lilis Renfiana; Misnen Ardiansyah; Alexander Thomaas Reed (Journal of Nusantara Economy, 2026)
Sharia-compliant status in Islamic capital markets is frequently interpreted as a comprehensive indicator of ethical conduct and sustainability, even though Sharia screening, Environmental, Social, and Governance (ESG) assessment, and Maqāsid -based Islamic ESG evaluate fundamentally different dimensions of corporate performance. This study investigates whether these three frameworks produce equivalent assessments for the same issuers and examines the governance implications arising from their divergence. Employing a qualitative directed content analysis supported by descriptive quantitative assessment, the research analyzes the audited financial statements, annual reports, and sustainability reports for fiscal year 2025 of 33 Indonesian non-financial issuers consistently listed in the Jakarta Islamic Index 70 (JII70) during 2021–2025. Sharia compliance is measured using publicly available proxies for interest-bearing debt and non-permissible income under multiple regulatory thresholds (45/10, 45/5, and 33/5), ESG disclosure is evaluated through 28 Indonesia Stock Exchange sustainability indicators, and Islamic ethical additionality is measured using 22 Maqasid-based Islamic ESG indicators. The findings reveal that although ESG disclosure and Maqāsid alignment demonstrate a strong positive relationship (r = 0.702; p < 0.001), the three assessment frameworks generate substantially different issuer rankings, compliance outcomes, and ethical profiles. Thirty-one issuers satisfy the transitional 45/10 threshold, declining to 30 under the 45/5 standard and 25 under the stricter 33/5 threshold, indicating that regulatory tightening materially alters the composition of Sharia-compliant investment universes. Average ESG performance reaches 69.82 out of 84, while Maqāsid alignment averages 54.45 out of 66, yet these relatively high scores do not necessarily correspond to stronger Sharia financial compliance. The study concludes that legal-financial permissibility, sustainability disclosure quality, and Islamic ethical additionality represent complementary rather than interchangeable dimensions of issuer evaluation. It contributes a layered accountability framework integrating Sharia screening, ESG disclosure, and Maqāsid -based assessment through a three-panel disclosure dashboard, offering a more transparent governance model for regulators, issuers, and investors in contemporary Islamic capital markets.